2018
DOI: 10.1128/iai.00486-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Plasmodium-Specific Carrier Protein To Enhance Production of RecombinantPfs25, a Leading Transmission-Blocking Vaccine Candidate

Abstract: Challenges with the production and suboptimal immunogenicity of malaria vaccine candidates have slowed the development of a multiantigen vaccine. Attempting to resolve these issues, we focused on the use of highly immunogenic merozoite surface protein 8 (MSP8) as a vaccine carrier protein. Previously, we showed that a genetic fusion of the C-terminal 19-kDa fragment of merozoite surface protein 1 (MSP1) to MSP8 (MSP8) facilitated antigen production and folding and the induction of neutralizing antibodies to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…Tfh cells are required for germinal center B cell differentiation into LLPC essential for long-lasting protection. Similar findings were subsequently reported by Parzych et al with the P. falciparum merozoite surface protein 8 (MSP8) tested as a carrier to deliver Pfs25 (Parzych et al, 2017). These reports highlighted the relevance of T cell epitopes present in the carrier proteins to promote robust immune responses.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Tfh cells are required for germinal center B cell differentiation into LLPC essential for long-lasting protection. Similar findings were subsequently reported by Parzych et al with the P. falciparum merozoite surface protein 8 (MSP8) tested as a carrier to deliver Pfs25 (Parzych et al, 2017). These reports highlighted the relevance of T cell epitopes present in the carrier proteins to promote robust immune responses.…”
Section: Discussionsupporting
confidence: 79%
“…A subsequent clinical trial using a protein-based Pvs25 formulated with Montanide ISA 51 as an adjuvant, showed that low doses of the formulation were able to induce transmission blocking immunity, but higher doses were associated with systemic adverse events (Wu et al, 2008). However, pre-clinical and clinical studies aimed at improving the suboptimal immunogenicity observed by immunization with the Plasmodium P25 proteins, Pfs25, and Pvs25 have suggested that the addition of a carrier protein could potentially enhance the immunogenicity of this protein (Qian et al, 2007; Parzych et al, 2017; Radtke et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…We then investigated the immunogenicity of the TatD-like DNase protein in combination with various adjuvants, including Montanide ISA 51 and 61, Alhydrogel, and levamisole. Previous studies indicated that Montanide ISA 51 is a strong Th-2 biased inducer ( Yazdani et al, 2004 ; Parzych et al, 2017 ). Here we found that mice immunized with Montanide ISA 51 as an adjuvant generated a higher level of antibody responses than those in the other groups (P < 0.01, Figure 4 ), and the mice showed significantly stronger protection than the mice immunized with the same antigen combined with other adjuvants ( Figure 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several antigens such as merozoite surface antigens from the asexual stage parasite have also been tested to inhibit parasite proliferation in human erythrocytes, but the clinical protection effect has been limited ( Matuschewski, 2017 ). The other approach was to block parasite development in the mosquito midgut by antibodies to the gametocytes and ookinetes ( Parzych et al, 2017 ). Further, immunization with mixed or arrays of multistage antigens has also been tried, but the protection has not been satisfactory ( Lyke, 2017 ; Matuschewski, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Most TBVs rely on host antibodies ingested during blood feeding, along with Plasmodium parasites, that bind to proteins on the surface of the parasite and block transmission by inhibiting parasite development ( Sauerwein and Bousema, 2015 ; Schorderet-Weber et al, 2017 ). Over the last 20 years, a number of antigens, including Pfs230 ( MacDonald et al, 2016 ; Marin-Mogollon et al, 2018 ; Scaria et al, 2019 ), Pfs48/45 ( Theisen et al, 2014 ; Singh et al, 2017 , 2019 ; Cao et al, 2018 ; Lennartz et al, 2018 ), and Pfs25 in Plasmodium falciparum as well as its ortholog Pvs25 in Plasmodium vivax ( Miura et al, 2007 ; Lee et al, 2016 ; Blagborough et al, 2016 ; Brune et al, 2016 ; Leneghan et al, 2017 ; Parzych et al, 2018 ; Thompson et al, 2018 ; McLeod et al, 2019 ; Yusuf et al, 2019 ), have been identified as potential vaccine targets. Preclinical and clinical studies have shown that TBVs hold the promise to reduce malaria transmission and raise the prospect of providing an additional effective tool toward malaria eradication ( Chichester et al, 2018 ; Sagara et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%